2022
DOI: 10.20944/preprints202201.0026.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biogas Production from Organic wastes and Iron as an Additive – A Short Review

Abstract: The world is facing a serious energy crisis and environmental pollution problems due to a sharp increase in the world population. Bioenergy is an eminent solution to these problems. Anaerobic digestion is a green energy technology used worldwide for the conversion of organic waste to biogas. It is reported that organic wastes are hard to digest and need some technical improvement in the anaerobic digestion process to improve biogas yield. Iron-based additives, due to their electron acceptance and donation capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Numerous studies have previously been reported for the treatment of effluents from various sectors, i.e. domestic, food processing, swine, winery, landfill leachate, makgeolli, sugar industry and paper industry 15‐22 . There have been only a few research papers published on the use of potato processing wastewater (PPW) as a substrate in MEC systems 19,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have previously been reported for the treatment of effluents from various sectors, i.e. domestic, food processing, swine, winery, landfill leachate, makgeolli, sugar industry and paper industry 15‐22 . There have been only a few research papers published on the use of potato processing wastewater (PPW) as a substrate in MEC systems 19,23 .…”
Section: Introductionmentioning
confidence: 99%
“…domestic, food processing, swine, winery, landfill leachate, makgeolli, sugar industry and paper industry. [15][16][17][18][19][20][21][22] There have been only a few research papers published on the use of potato processing wastewater (PPW) as a substrate in MEC systems. 19,23 However, PPW has various distinct benefits that set it apart from other types of wastewaters as a potential substrate for MECs.…”
Section: Introductionmentioning
confidence: 99%